Steroid-Sparing effects of pentoxifylline in pulmonary sarcoidosis - Park, M.K.; Fontana, J.R.; Babaali, et al., H. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background: Agents that target pro-inflammatory cytokines may be useful in pulmonary sarcoidosis. Objective: To determine effectiveness of a non-selective cyclic nucleotide phosphodiesterase (PDE) inhibitor, pentoxifylline (POF). Design: Randomized, double-blind, placebo-controlled trial, Setting: Clinical Research Center, National Institutes of Health. Patients: 27 patients with biopsy-confirmed pulmonary sarcoidosis receiving prednisone. Intervention: Placebo or POF (1200-2000 mg/day) for 10 months, as prednisone was tapered. Measurements: Primary endpoints: sustained improvement in two or more pulmonary function parameters, or a combination of one pulmonary function parameter and dyspnea. Results: Except for one patient, primary endpoints were not reached in POF-treated patients. Therefore, a post hoc analysis was performed. The observed relative risk reduction for flares associated with POF treatment was 54.9% (95% CI 0.21, 0.89) and the absolute risk reduction was 50.6% (95% CI 0.22, 0.80). Compared to placebo treatment, in the POF group, the mean prednisone dose was lower at 8 and 10 months (p = 0.007 and 0.01 respectively), and there was a trend towards less prednisone usage over the entire study period (p = 0.053), as determined by cumulative change analysis. Conclusions: Although our exploratory post hoc analysis suggested that POF reduced flares and had steroid-sparing effects, given the study limitations, definitive conclusions cannot be drawn regarding the efficacy of POF in pulmonary sarcoidosis. In addition, gastrointestinal side-effects, at the doses used, would seem to limit the use of POF in treating pulmonary sarcoidosis. Overall, however, this trial may provide a basis for using more specific, better-tolerated, PDE inhibitors in future clinical trials.